U.S. international exhibitions during the Cold War winning hearts and minds through cultural diplomacy - Wulf, Andrew James 1971- (Rowman & Littlefield, 2015)
This book advances an understanding of cultural diplomacy that examines a single area of government and private sector partnership, and what became in the mid-twentieth century the most prominent manifestation of this alliance-the cultural exhibitions sent abroad to "tell America's story" with the goal of "winning hearts and minds."